Development of an Instrument to Map Acid–Base Misconceptions among High-Achieving Senior High School Students in Eastern Indonesia - Wiwin Putriawati; Saraswati Haylian Chiani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Acid–base misconceptions remain a persistent challenge in high school chemistry, particularly among high-achieving students in Eastern Indonesia, where instructional strategies often emphasize procedural knowledge over conceptual understanding. Mapping these misconceptions is critical to designing differentiated remediation strategies that promote deep conceptual change. This study aims to map students' misconceptions by developing a diagnostic test instrument named the Acid–Base Misconception Diagnostic Test Instrument (IDM-AB). Research data were obtained through expert validation (three chemistry education experts) and empirical testing, analyzed descriptively using SPSS. Instrument validation included content, construct, and language validity, item analysis (difficulty and point-biserial correlation), and internal consistency reliability (Cronbach's alpha = 0.905). The classification of misconceptions was based on the Certainty of Response Index (CRI) with a cutoff of 2.5. The pilot test involved 121 students, and the final test was administered to 123 students. Results show: (1) the IDM-AB instrument meets both theoretical and empirical validity standards; (2) student misconception levels were distributed as follows: moderate (42.86%, 51 students), high (37.82%, 45 students), and low (19.33%, 23 students). Students with high misconceptions require intensive conceptual correction, while those with low misconceptions show potential for scientific conceptual change. This mapping provides a foundation for implementing targeted, concept-specific remediation strategies to address persistent alternative conceptions in acid-base chemistry.